2022
DOI: 10.1097/jova.0000000000000036
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Adult Patients With Vascular Anomalies Reveals Acute Need of Adult Hematologists-Oncologists to Enter the Field

Abstract: Background: We have observed that adult patients with vascular anomalies often have limited access to specialists with expertise in vascular anomalies who can coordinate their care and prescribe medications, but evidence-supported statistics needed for advocacy efforts was not available. Methods: An anonymous survey was formulated for adult patients with vascular anomalies, in collaboration with patient advocacy groups. The survey included 50 questions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…4,5 One study of 249 adults with VAs found that of the participants still receiving pediatric care, 97% had no plan for transfer to an adult provider. 1 Of those no longer in a pediatric setting, 34% were unable to find a physician. Forty-five percent had no consistent care provider, and 60% were seeing providers without specific training in the management of VAs.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…4,5 One study of 249 adults with VAs found that of the participants still receiving pediatric care, 97% had no plan for transfer to an adult provider. 1 Of those no longer in a pediatric setting, 34% were unable to find a physician. Forty-five percent had no consistent care provider, and 60% were seeing providers without specific training in the management of VAs.…”
Section: Discussionmentioning
confidence: 99%
“…Forty-five percent had no consistent care provider, and 60% were seeing providers without specific training in the management of VAs. 1 Without formalized TOC programs, there may be fewer opportunities for interdisciplinary coordination among adolescent and adult specialists, resulting in a failure to provide comparable care to adult patients with VAs. Our results demonstrate the lack of TOC programs and variable patient care trajectories for patients with VAs as they mature, despite the existence of well-established VACs within academic medical centers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations